2019
DOI: 10.3390/nu11122953
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Concentrations and Synergy between Retinol, β-Carotene, and Zinc According to Cancer Staging and Different Treatment Modalities Prior to Radiation Therapy in Women with Breast Cancer

Abstract: The procedures used for breast cancer treatment are able to increase the level of oxidative stress and cause depletion of antioxidants. Objectives: To investigate the relationship between serum concentrations of retinol, β-carotene, and zinc, according to breast cancer staging, considering different treatment modalities prior to radiation therapy and the synergistic action between these micronutrients. Methods: This is a cross-sectional observational study comprising a cohort of patients with breast cancer whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
0
8
1
Order By: Relevance
“…However, an inverse association between plasma retinol and both carotenoids and tocopherol was found in this study. The mean concentration of β-carotene found in this study (521,8 + 450 µg/L) was higher than the plasmatic concentration previously reported in a similar study, which described a concentration ranging from 171.11 ± 180.2 to 227.1 ± 157.8 µg/L, depending on the stage of the BC [ 41 ], and the mean values of 329.3 µg/L described for the women enrolled in the Italian cohorts of the European Prospective Investigation into Cancer and Nutrition [ 40 ]. These results were consistent with adherence to the MD, which is based on a high intake of plant foods and low consumption of animal foods.…”
Section: Discussioncontrasting
confidence: 81%
“…However, an inverse association between plasma retinol and both carotenoids and tocopherol was found in this study. The mean concentration of β-carotene found in this study (521,8 + 450 µg/L) was higher than the plasmatic concentration previously reported in a similar study, which described a concentration ranging from 171.11 ± 180.2 to 227.1 ± 157.8 µg/L, depending on the stage of the BC [ 41 ], and the mean values of 329.3 µg/L described for the women enrolled in the Italian cohorts of the European Prospective Investigation into Cancer and Nutrition [ 40 ]. These results were consistent with adherence to the MD, which is based on a high intake of plant foods and low consumption of animal foods.…”
Section: Discussioncontrasting
confidence: 81%
“…The low level of micronutrients such selenium or zinc, observed in COVID-19 populations compared to control populations, does not necessarily imply pre-existing deficiencies favoring the occurrence of the disease [ 48 , 49 ]. As has been shown in the treatment of certain cancers, it is also possible that COVID-19 itself leads to an alteration in micronutrient status [ 50 ]. For example, the combination of hypoxia and IL-6 suppresses selenoprotein expression (such as glutathione peroxidase), causing whole-body selenium status decline and an increased generation of reactive oxygen species [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous human studies have reported that reduced levels of β-carotene can be detected in patients with different cancers, including oral cancer [398], breast cancer [399], prostate cancer [400], pancreatic cancer [338], and malignant pleural mesothelioma [401]. Moreover, numerous epidemiological studies have indicated that dietary intakes of βcarotene, obtained from fruits and vegetables, may reduce cancer mortality [402] and protect against the development of some gastrointestinal cancers, such as esophageal cancer [318], gastric cancer [316], colon cancer [312], pancreatic cancer, and hepatocellular carcinoma [314,324].…”
Section: Human Studiesmentioning
confidence: 99%